The assessment of liver function test and fertility hormones in Saudi athletes using anabolic androgenic steroids - Shatha Jambi; Ahmed Mirza; Torki Zughaibi; Haitham Khalil; Anwar Borai (Elsevier, 2024)
Background: A growing number of athletes are using synthetic anabolic-androgenic steroids (AAS), comprised of testosterone and other derivatives, to enhance athletic performance and muscle mass. Over the years, numerous reports elucidated the side effects of the illegal use of AAS, such as infertility, and liver disorders. The effect of AAS on the hepatic and reproductive systems in Saudi athletes has not yet been studied. Therefore, this study examined the liver function and sex hormone parameters of AAS users as compared to non-users. Methods: Fasting blood samples were collected from 16 male Saudi athletes, 10 AAS-users (cases) and 6 non-users (controls) to measure liver function tests (ALT, AST, GGT, ALP, total protein, albumin, direct and total bilirubin) and muscle enzymes (CK, LDH), Fertility hormones (LH, FSH, total testosterone, estradiol, and prolactin) were included also. Furthermore, a self-reported questionnaire was obtained to identify the type of AAS used, the dosage, and the length of the course before sample collection. Results: The results show a statistically significant increase in ALT (P < 0.001), AST (P < 0.001), CK (P < 0.05), and a significant decrease (P < 0.05) in albumin (P < 0.001) and total bilirubin levels (P < 0.01) in AAS-users. Total testosterone increased significantly among AAS (P < 0.05), along with a significant decrease in LH (P < 0.01), and FSH (P < 0.001) levels, while serum prolactin and estradiol levels were significantly increased (P < 0.05). Conclusion: AAS can enhance physical performance and appearance, its potential adverse effects on the hepatic and reproductive systems necessitate careful consideration. Our research demonstrates an increase in the liver-specific enzyme ALT in AAS users relative to non-users and the possibility that short-term AAS usage increases the risk of liver injury.